Hybrid heuristic for multi-carrier transportation plans - Landa-Silva, Dario; Wang, Yijun; Donovan, Paul; Kendall, Graham (2011)
This paper describes a hybrid heuristic approach to construct transportation plans for a singlecustomer multi-carrier scenario that arises at 3T Logistics Ltd, a UK company that provides outsourced transportation planning and management services. The problem consists on planning the delivery, using a set of carrier companies, of a set of shipments from a warehouse to different consignees across the UK. The problem tackled resembles a vehicle routing problem with time windows but there are several differences in our scenario. The hybrid heuristic algorithm described here combines a clustering algorithm, constructive and local search heuristics, and exact assignment based on integer programming. This approach is being currently evaluated at the company and results so far indicate the suitability of the algorithm to produce practical transportation plans at reduced cost compared to current practice.